Analysis of Wear in the Contact Between the Wheel Tread and the Rail Head: Influence of the Manufacturing Process of Cast and Forged Railway Wheels - V.G. Germinari; R.S. Miranda; A.B. Rezende; A.C. Carvalho; D.S. Monteiro; M. Jose-Bueno; R.C. Rocha; A. Sinatora; P.R. Mei (Materials Research, 2025)
In countries with continental dimensions like Brazil, railways transport production from inland regions to ports and the international market. It is essential to note that researchers and engineers in the railway sector are constantly striving to reduce operational and maintenance costs associated with wheel-rail contact while maintaining high standards of quality, safety, and operational predictability. In this context, wheels are one of the most costly components in railway acquisition and maintenance, representing a significant factor in transport safety. Additionally, their manufacturing process can involve either forging or casting. Therefore, the manufacturing process can offer the best cost-benefit ratio to meet the diverse demands of the railway sector — longer wear/fatigue life with lower costs. This study aimed to analyze the effects of the manufacturing process of the cast and forged microalloyed railway wheels, with similar microstructure, hardness, and equivalent carbon content, on the metallurgical defects formation and tribological properties. To support material characterization, optical microscopy, scanning electron microscopy, hardness measurements, ASTM E45 standards for evaluating metallurgical defects, twin-disc wear tests, Raman spectroscopy, and statistical analyses were conducted to compare the defects and cracks developed in railway steels.